Efeitos da acupuntura no tratamento de dor lombar em gestantes - Martins, Eveliny Silva (2017)
In the spine triggers one of the most disabling symptoms in an individual: low back pain. Lumbar pain related to pregnancy has gained more importance due to the impact and impact on the quality of life of the pregnant woman, which may be incapacitating, limiting daily activities and should not be ignored without treatment. A therapy for low back pain during pregnancy is acupuncture, this being a health intervention technology, originating from traditional Chinese medicine that involves a set of procedures that are based on the stimulation of precise anatomical points of the body, defined through the insertion of Metal filiform needles to aid in the promotion, maintenance and recovery of health. The objective of this study was to evaluate the effects of acupuncture in the treatment of low back pain in pregnant women in the second and third gestational trimesters. Almost experimental study, before and after, occurred in the period from June to October 2016, at the Federal University of Ceará. All pregnant women with complaints of low back pain, with gestational age between 14 and 37 weeks participated in the study. Six sessions were performed, being twice a week, with 30 minutes each, with the application of systemic and auricular points. The Visual Analog Scale and the McGill questionnaire were used to assess the pain, as well as the sociodemographic, clinical and obstetrical identification tool. Statistical analysis and cross-checking of variables were performed in order to verify statistical associations through SPSS software version 21.0. At the end of the study, 242 acupuncture sessions were performed, and 56 women with low back pain were included in the study. There was a statistically significant reduction (p <0.05) in the scores, descriptors and pain index of the instruments applied. Mean pain scores decreased in the second (4.92), fourth (3.24) and sixth (1.00) sessions. The entire sample had a more than 50% reduction in pain. Some women had their pain ceased before completing the six sessions and there was improvement in activities impaired by pain after treatment in all pregnant women. In addition to lower back pain, the pregnant women referred to perceived improvements in other aspects, such as: relaxation, stress, headache, anxiety, mood and mood. No serious adverse events were reported in the treatment. It was evidenced that acupuncture provided favorable positive effects to the participants' health, since there was a reduction in pain right from the second session and presented a gradual decrease with the advancement of the number of sessions.